Multiscale Hybridization of Natural Silk–Nanocellulose Fibrous Composites With Exceptional Mechanical Properties - Eom, Jungju; Park, Subong; Jin, Hyoung-Joon; Kwak, Hyo Won (Frontiers in Materials, 2020)
Because of the crisis of the petrochemical era, environmentally friendly natural polymers and related material processes are receiving great attention. Cellulose and silk are typical fibrous materials that consist of polysaccharides and proteins, respectively, and have excellent mechanical properties and high physicochemical stabilities due to their unique self-assembly-based hierarchical structures. In this study, highly stable high-strength silk fiber (SF)–cellulose nanofibril (CNF) composites were prepared by the hierarchical fusion of micrometer-scale SFs and nanometer-scale CNFs. This manufacturing process is cost-effective because the raw materials (SFs and CNFs) are used as is. It is an eco-friendly process because it does not require the use of organic solvents or toxic reagents. In addition, it is an energy-efficient process because heat fusion (120 °C) takes only 10 min. The results of the Direct Red 80 staining experiments confirm that up to 15 wt.% CNFs were added to the SF nonwoven. With the increase in the CNF amount, the nanometer-scale CNFs form a coating on the micro-scale SFs. At the same time, the CNFs form bonds with the SFs and increase the interfibrillar bonding strength of the CNF-coated SFs. Therefore, the mechanical properties of the SF/CNF composite and its stability in the water environment rapidly increase with increasing CNF concentration. In the case of SF/CNF15, the mechanical and impact strengths increase by 110% and 228%, respectively, compared with SF nonwoven without CNF. In addition, as CNFs are introduced, hydrophobicity of the surface and bulk of the SF/CNF composite can be imparted, thereby maintaining its structural stability in the water environment. This eco-friendly SF/CNF composite can be widely used as a reinforcement preform of fiber-reinforced plastics as well as for other applications in the fibrous composite industry.